Methodology of Lexical Competence Formation of Power-Engineering Students based on CBA and its Experimental Research in Teaching ESP - Botiraliyevna, Bakirova Khilolakhon (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This article considers about methodology of lexical competence formation of power - engineering students and its experimental research in ESP teaching. Here some theoretical approaches are discussed, and new methodology suggested by the author is tested in practice. Experimental work was carried out in 3 non-philological universities of the Republic of Uzbekistan as Tashkent State Technical University named after Islam Karimov (TSTU), Fergana Polytechnic Institute (FerPI) and Navoi State Mining Institute (NSMI). Anonymous questionnaires were obtained from students and teachers, written control works are received from students. Using the results obtained, the existing difficulties in teaching and mastering the terms of power engineering were identified. With the help of these difficulties there have been developed a typology of exercises aimed at overcoming the identified challenges. The exercises given here were prepared and published in the textbook "Foreign language for 3rd year power engineering students" for the development of lexical competence, used at English language course for students of the 3rd year of the Faculty of "Power engineering" of non-philological higher educational institutions of the republic. The texts in the manual is based on the content of teaching special subjects and textbooks in the field of power engineering of TSTU, 3rd year "Foreign language" educational and methodological complex, O.G.Smirnova, E.A. Protsukovich's e-book English for Power Engineering, David Bonamy's Technical English 1, and Internet sources. Besides this there are given some recommendations and suggestions on teaching technical terms to ESP students in higher educational establishments.